Credit Growth and Financial Stability in the Czech Republic - Frait, Jan; Gersl, Adam; Seidler, Jakub (2012)
The Czech Republic had experienced a credit boom similar to those in other converging economies in the pre-crisis years. Nevertheless, the consequences of this credit boom were limited as was the impact of the global crisis on domestic financial institutions. This paper describes the developments in the Czech banking sector and explains how the tough macroeconomic environment in the Czech Republic acted as a strong tool of macroprudential policy. It concludes that although it is difficult to tame credit booms in small converging economies, a concerted set of microprudential and macroprudential measures, including monetary and fiscal ones, may ensure some success.